Guanxinning attenuates diabetic myocardial ischemia–reperfusion injury by targeting oral Fusobacterium nucleatum and modulating PTEN signaling - Li, Yiwen; Xu, Qian; Liu, Yanfei; Liu, Longkun; Wang, Wenting; Zhu, Mengmeng; Cui, Jing; Yang, Hongjun; Liu, Yue (Frontiers in Pharmacology, 2025)
BackgroundThe incidence and severity of diabetic myocardial ischemia reperfusion injury (DMIRI) are increasing, highlighting the urgent need for effective prevention and treatment. Previous studies have revealed that specific oral microbiota (Fusobacterium nucleatum) are closely involved in DMIRI, potentially serving as therapeutic targets. Guanxinning (GXN) has shown significant efficacy in treating diabetic cardiomyopathy. However, its mechanisms of action regarding DMIRI and its relationship with specific microbiota remain to be elucidated.ProposalThis study investigates whether GXN alleviates DMIRI by modulating F. nucleatum and host interactions.MethodsThe effects of GXN on cardiac injury, cardiac protein expression and the abundance of F. nucleatum were evaluated in C57BL/6 mice under both conventional and germ-free conditions. GWAS analysis was employed to identify potential mechanisms linking F. nucleatum and DMIRI. Fusobacterium nucleatum IgG levels were measured, and LC-MS/MS metabolomics along with Metorigin trace-ability analysis were conducted to validate the proposed mechanisms.ResultsGXN treatment significantly reduced myocardial injury in diabetic mice and decreased oral F. nucleatum abundance, although its effects on other gut microbiota taxa were variable. Importantly, the cardioprotective efficacy of GXN was markedly attenuated under pseudo-germ-free conditions, suggesting that its benefits are at least partly microbiota-dependent. PI3K signaling pathway was identified as a central mediator of the microbiota interaction in DMIRI. Correspondingly, cardiac tissues from diabetic mice exhibited reduced expression of PTEN, consistent with pathway activation. Notably, F. nucleatum exposure elevated plasma levels of specific anti–F. nucleatum IgG antibodies and appeared to influence the host PI3K pathway through modulation of phenylalanine metabolism.ConclusionGXN may alleviate DMIRI by targeting F. nucleatum and PTEN related pathways, offering new insights into microbiota-based cardio protection.